Clinical characteristics of metabolic syndrome in Korea, and its comparison with other Asian countries. Issue 5 (7th January 2015) - Hong, A Ram; Lim, Soo
Abstract Metabolic syndrome is referred to as syndrome X or insulin resistance syndrome, and is primarily composed of abdominal obesity, diabetes, glucose intolerance, dyslipidemia and high blood pressure. Asians have a lower frequency of obesity than Caucasians, but have an increasing tendency toward metabolic syndrome. Thus, metabolic syndrome poses a major challenge for public health professionals, and is set to become a social and economic problem in Asian populations. Most data on metabolic syndrome are based on studies from Western countries with only limited information derived from Asian populations. Recently, several studies were carried out on a large scale that represents the general Korean population. The prevalence of metabolic syndrome in Korean adults has varied depending on the study designs and different criteria, but shows a distinct increasing trend of metabolic syndrome driven by an increase in abdominal obesity and dyslipidemia. Given the rapid economic progression of Korea over the past 30 years along with a rise of the aged population, it is expected that the prevalence of metabolic syndrome will further increase. Therefore, a proactive strategy at the governmental level for metabolic syndrome prevention should be implemented, reducing abdominal obesity and dyslipidemia. Healthy dietary habits and regular exercise should be emphasized as a part of such a strategy.